Intersectional analysis of Advanced Placement Physics participation and performance by gender and ethnicity - Robert Krakehl (American Physical Society, 2021)
Access and performance in advanced high school physics have been persistently inequitable when considering student ethnicity and gender. This quasiexperimental, observational study examined access and performance of students in four Advanced Placement (AP) Physics courses in 2018–2019: AP Physics 1 (N=150 451), AP Physics 2 (N=20 466), AP Physics C Mechanics (N=49 951), and AP Physics C Electricity & Magnetism (N=21 602); this analysis utilized an intersectional lens of ethnicity and gender in identifying enrollment and performance disparities. Descriptive and inferential analyses were conducted to determine whether the distribution of student ethnicities and genders of students who took the examinations was similar to that of U.S. schools. Further analyses were conducted to determine whether achievement on AP Physics examinations varied by 14 unique intersectional groups characterized by gender and ethnicity. Results indicated that AP Physics 1 was a relatively accessible course, though enrollment disparities among genders, ethnicities, and intersectional groups grew as the AP Physics courses became more advanced with physics and/or calculus prerequisites or corequisites. There were large decreases in course enrollments from first- to second-year AP Physics courses, particularly for women who were also underrepresented ethnic minorities. In terms of performance, AP Physics 1 had the lowest overall weighted average, with the majority of students failing the examination. Women who were traditionally underrepresented ethnic minorities were found to have failure rates of over 80% on the AP Physics 1 examination, and failure rates near 50% for AP Physics 2 and the AP Physics C courses compared to nonminority men who had approximately half the failure rates. In most cases, men outperformed women who shared their ethnicities. These results present opportunities for physics education policy makers and researchers to design interventions for students in intersecting marginalized social groups, many of whom have disproportionately low representation and achievement in advanced high school physics, which occurs at a critical juncture in the physics pipeline.